Subtypes of depression and their overlap in a naturalistic inpatient sample of major depressive disorder. Issue 1 (14th June 2017) - Musil, Richard; Seemüller, Florian; Meyer, Sebastian; Spellmann, Ilja; Adli, Mazda; Bauer, Michael; Kronmüller, Klaus‐Thomas; Brieger, Peter; Laux, Gerd; Bender, Wolfram; Heuser, Isabella; Fisher, Robert; et al.
Abstract: Subtyping depression is important in order to further delineate biological causes of depressive syndromes. The aim of this study was to evaluate clinical and outcome characteristics of distinct subtypes of depression and to assess proportion and features of patients fulfilling criteria for more than one subtype. Melancholic, atypical and anxious subtypes of depression were assessed in a naturalistic sample of 833 inpatients using DSM‐IV specifiers based on operationalized criteria. Baseline characteristics and outcome criteria at discharge were compared between distinct subtypes and their overlap. A substantial proportion of patients (16%) were classified with more than one subtype of depression, 28% were of the distinct anxious, 7% of the distinct atypical and 5% of the distinct melancholic subtype. Distinct melancholic patients had shortest duration of episode, highest baseline depression severity, but were more often early improvers; distinct anxious patients had higher NEO‐Five Factor Inventory (NEO‐FFI) neuroticism scores compared with patients with unspecific subtype. Melancholic patients with overlap of anxious features had worse treatment outcome compared to distinct melancholic and distinct anxious subtype. Distinct subtypes differed in only few variables and patients with overlap of depression subtypes may have independent clinical and outcome characteristics. Studies investigating biological causes of subtypes of depression should take influence of features of other subtypes into account.